Mantas de fibras poliméricas eletrofiadas baseadas em poli(ácido láctico)(PLA) e borracha natural contendo curcumina visando aplicações como curativo cutâneo - Chagas, Paulo Augusto Marques (2021)
Although the use of antibiotics has been indispensable for the control of diseases in humans and animals, their indiscriminate consumption has favored the appearance of bacteria resistant to antibiotics. A way to tackle this problem is based on the use of natural compounds with antibacterial properties, as an alternative to conventional antibiotics, due to their different mechanisms of action. In this context, this work aimed at the development of electrospun fiber mats of poly lactic acid (PLA) containing natural rubber (NR) and curcumin for applications in bactericidal wound dressings. PLA was chosen as the base polymer for fiber production because it is easily electrospun, besides being biocompatible and biodegradable, while latex (containing NR) was chosen due to its natural stimulus to angiogenesis, biocompatibility, low cost and easy handling. Curcumin was chosen because of their antibacterial, antioxidant, antifungal and anti-inflammatory properties. Due to the incompatibility between the polymers, the NR epoxidation reaction was used to favor the interaction with the PLA. Microfibers from the blend of PLA and NR (without the compatibility process) were also produced with two concentrations of curcumin (2.5% an d 5%, in relation to the polymeric mass), using an asymmetric membrane structure (anisotropic structure composed of 2 layers of fibers with different properties in terms of morphology and properties) aiming at application in wound dressing. The results indicated that the asymmetrical mat containing curcumin showed antibacterial action against S. aureus and E. coli bacteria, with more promising results for the former, according to the results of a wound model using ex-vivo pigskin. The results also showed that the asymmetric membranes were able to prevent the penetration of bacteria for up to 14 days. In addition, photodegradation, one of the main disadvantages of curcumin, was overcome with the addition of an extra top layer of PLA nanofibers over the curcumin-containing PLA/NR microfiber layer, which was able to prevent its photodegradation for up to 12 hours when exposed to light. Finally, the results presented show two different alternatives for obtaining microfibers using the blend of NR and PLA and also the high potential use of curcumin for wound dressing application.